Demon copperhead eaudiobook A novel. - Kingsolver, Barbara (HarperAudio, 2022)
WINNER OF THE PULITZER PRIZE WINNER OF THE WOMEN'S PRIZE FOR FICTION New York Times Readers' Pick: Top 100 Books of the 21 st Century An Oprah's Book Club Selection An Instant New York Times Bestseller An Instant Wall Street Journal Bestseller A #1 Washington Post Bestseller A New York Times ""Ten Best Books of the Year"" ""Demon is a voice for the ages—akin to Huck Finn or Holden Caulfield—only even more resilient." —Beth Macy, author of Dopesick ""May be the best novel of [the year]. . . . Equal parts hilarious and heartbreaking, this is the story of an irrepressible boy nobody wants, but readers will love." — Ron Charles, Washington Post From the acclaimed author of The Poisonwood Bible and The Bean Trees and the recipient of the National Book Foundation's Medal for Distinguished Contribution to American Letters, a brilliant novel that enthralls, compels, and captures the heart as it evokes a young hero's unforgettable journey to maturity Set in the mountains of southern Appalachia, Demon Copperhead is the story of a boy born to a teenaged single mother in a single-wide trailer, with no assets beyond his dead father's good looks and copper-colored hair, a caustic wit, and a fierce talent for survival. Relayed in his own unsparing voice, Demon braves the modern perils of foster care, child labor, derelict schools, athletic success, addiction, disastrous loves, and crushing losses. Through all of it, he reckons with his own invisibility in a popular culture where even the superheroes have abandoned rural people in favor of cities. Many generations ago, Charles Dickens wrote David Copperfield from his experience as a survivor of institutional poverty and its damages to children in his society. Those problems have yet to be solved in ours. Dickens is not a prerequisite for readers of this novel, but he provided its inspiration. In transposing a Victorian epic novel to the contemporary American South, Barbara Kingsolver enlists Dickens' anger and compassion, and above all, his faith in the transformative powers of a good story. Demon Copperhead speaks for a new generation of lost boys, and all those born into beautiful, cursed places they can't imagine leaving behind.